The Interleukine-17 Cytokine Family: Role in Development and Progression of Spondyloarthritis, Current and Potential Therapeutic Inhibitors - Anna Davydova; Yuliya Kurochkina; Veronika Goncharova; Mariya Vorobyeva; Maksim Korolev (Biomedicines, 2023)
Spondyloarthritis (SpA) encompasses a group of chronic inflammatory rheumatic diseases with a predilection for the spinal and sacroiliac joints, which include axial spondyloarthritis, psoriatic arthritis, reactive arthritis, arthritis associated with chronic inflammatory bowel disease, and undifferentiated spondyloarthritis. The prevalence of SpA in the population varies from 0.5 to 2%, most commonly affecting young people. Spondyloarthritis pathogenesis is related to the hyperproduction of proinflammatory cytokines (TNFα, IL-17A, IL-23, etc.). IL-17A plays a key role in the pathogenesis of spondyloarthritis (inflammation maintenance, syndesmophites formation and radiographic progression, enthesites and anterior uveitis development, etc.). Targeted anti-IL17 therapies have established themselves as the most efficient therapies in SpA treatment. The present review summarizes literature data on the role of the IL-17 family in the pathogenesis of SpA and analyzes existing therapeutic strategies for IL-17 suppression with monoclonal antibodies and Janus kinase inhibitors. We also consider alternative targeted strategies, such as the use of other small-molecule inhibitors, therapeutic nucleic acids, or affibodies. We discuss advantages and pitfalls of these approaches and the future prospects of each method.